Orality and Literacy: The Technologizing of the World - Ong, Walter J. (Abingdon, Oxon Routledge, 2002)
This classic work explores the vast differences between oral and literate cultures offering a very clear account of the intellectual, literary and social effects of writing, print and electronic technology.In the course of his study, Walter J. Ong offers fascinating insights into oral genres across the globe and through time, and examines the rise of abstract philosophical and scientific thinking. He considers the impact of orality-literacy studies not only on literary criticism and theory but on our very understanding of what it is to be a human being, conscious of self and other.This is a book no reader, writer or speaker should be without.
Keywords: Philosophy; Technology